2020
DOI: 10.1002/ase.1961
|View full text |Cite
|
Sign up to set email alerts
|

Dry Skulls and Cone Beam Computed Tomography (CBCT) for Teaching Orofacial Bone Anatomy to Undergraduate Dental Students

Abstract: Learning bone anatomy of the skull is a complex topic involving three‐dimensional information. The impact of the use of human dry skulls and cone beam computed tomography (CBCT) imaging was investigated in the teaching of undergraduate dental students. Sixty‐four first‐year students in the University of Hong Kong were randomly divided into eight groups. Four teaching methods were tested: (1) CBCT followed by standard lecture, (2) CBCT followed by lecture with skulls, (3) standard lecture followed by CBCT, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 45 publications
1
16
0
Order By: Relevance
“…It also corresponded in full to the syllabus of the dental anatomy unit. The learning outcomes were analyzed according to the literature (Zahra and Dunton, 2017;de Azevedo et al, 2018;Kulasegaram and Rangachari, 2018;Savoldi et al, 2021), allowing statistical differences (P < 0.001) between the methods. The T2 showed that the higher learning outcome, in theoretical (75.12% ±6.15) and spatial orientation (68.75% The data analysis was performed on the T1 cohort (face-to-face lecture with physical model) and T2 cohort (webinar lecture with CBCT image) using learning outcomes in the theoretical and spatial orientation contexts.…”
Section: Descriptive Analysis Of the Learning Outcomesmentioning
confidence: 99%
“…It also corresponded in full to the syllabus of the dental anatomy unit. The learning outcomes were analyzed according to the literature (Zahra and Dunton, 2017;de Azevedo et al, 2018;Kulasegaram and Rangachari, 2018;Savoldi et al, 2021), allowing statistical differences (P < 0.001) between the methods. The T2 showed that the higher learning outcome, in theoretical (75.12% ±6.15) and spatial orientation (68.75% The data analysis was performed on the T1 cohort (face-to-face lecture with physical model) and T2 cohort (webinar lecture with CBCT image) using learning outcomes in the theoretical and spatial orientation contexts.…”
Section: Descriptive Analysis Of the Learning Outcomesmentioning
confidence: 99%
“…The Collection is comprised of 368 individuals, including cranial remains of 260 individuals and postcranial remains of 248 individuals (Table 1, Figure 4(a)) (Savoldi et al, 2021). Note that not all the cranial remains have the corresponding postcranial remains and vice versa.…”
Section: Current Composition Of the Collectionmentioning
confidence: 99%
“…Lastly, alterations of the morphology of ear ossicles can be associated with congenital anomalies (Caparosa & Klassen, 1966) and syndromes (Black et al, 1975), or can be relevant for understanding the history of disease such as otitis media (Quam & Rak, 2008). Future research may also include morphological assessments using maxillofacial imaging of neurovascular foramina (von Arx et al, 2013), and investigation of new methods for the teaching of bone anatomy of the head (Savoldi, Yeung, et al, 2021).…”
Section: Future Use and Researchmentioning
confidence: 99%
See 2 more Smart Citations